Ład przestrzenny jako czynnik rozwoju lokalnego - Polska, Anna (Space Order as a Factor of Local Development, 2006)
In the rationally conducted space economy, including the local one, the main purpose is the systematic improvement of a space order, including the control of investors' behavior. Investors' behavior creates a relatively stable elements in space and forms in fact its image. Space order is precondition of this image, although it is difficult to define it accurately. In statutory formulation it can be defined as a space configuration, which creates a harmonious whole and in arranged relations takes into account all possible factors, and functional, socio-economic, ecological, cultural and composi-tion-esthetical demands. Space order, therefore, is a complicated notion. The definition, given above, has shown its nš aspects: ecological, social (living conditions and values' systems), economic, functional and esta-ical. Ecological order means the improvement of the conditions of environments' functioning and strengthening its state, including the ability to reconstruct resources and values. Order in social living conditions determines the satisfaction of all possible material and mental human needs. Economic order creates conditions for low costs of the economies' development and functioning in a given space. One can also add functional and esthetical orders to these aspects. Functional order is associated with a space coordination of different stable elements of natural, social and economic space. IK essence is the efficiency of functioning and development of particular domains in a given area, Lasi but not the least, esthetical order makes a space emotionally "good looking" from the point of view of the human needs. Its makes it more friendly for a public life. Space order is a favourable condition of economic development. It intensifies the level of interests in the area by different real and potential users, including inhabitants, newcomers and investors, Therefore the policy of economic development should be conducted at communities' (gminas') and other units' levels of public administration and also it should be integrated with a space policy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 317-326